2020
DOI: 10.1093/jxb/eraa132
|View full text |Cite
|
Sign up to set email alerts
|

Mild drought in the vegetative stage induces phenotypic, gene expression, and DNA methylation plasticity in Arabidopsis but no transgenerational effects

Abstract: There is renewed interest in whether environmentally induced changes in phenotypes can be heritable. In plants, heritable trait variation can occur without DNA sequence mutations through epigenetic mechanisms involving DNA methylation. However, it remains unknown whether this alternative system of inheritance responds to environmental changes and if it can provide a rapid way for plants to generate adaptive heritable phenotypic variation. To assess potential transgenerational effects induced by the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 93 publications
2
65
0
Order By: Relevance
“…2016), and A. thaliana responds to these cues experienced by parents and by the progeny themselves (Kendall and Penfield 2012; Kerdaffrec and Nordborg 2017; Lampei 2018; Van Dooren et al. 2020; Vayda et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2016), and A. thaliana responds to these cues experienced by parents and by the progeny themselves (Kendall and Penfield 2012; Kerdaffrec and Nordborg 2017; Lampei 2018; Van Dooren et al. 2020; Vayda et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Several genotypes, however, cycle quickly through life stages, allowing two generations in a year. The timing of critical life-stage transitions that determine overall life cycle expression, such as germination, flowering, and seed dispersal, relies on seasonal cueing (Zhang and Lechowicz 1994;Callahan and Pigliucci 2002;Fournier-Level et al 2016), and A. thaliana responds to these cues experienced by parents and by the progeny themselves (Kendall and Penfield 2012;Kerdaffrec and Nordborg 2017;Lampei 2018;Van Dooren et al 2020;Vayda et al 2018).…”
Section: The Study System and Traits Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought is one of the major abiotic environmental factors that, in combination with high insolation and high temperatures, often cause detrimental losses in crop productivity [ 1 , 2 , 3 ]. In nature, plants often face a mild drought combined with other factors, thus the effect of solely water deficit is masked by the other two stresses—heat and photo-oxidation [ 4 ]. Yield productivity is affected by climate changes, which involve repeated occurrences of limited water supply combined with elevated CO 2 and high temperature, generating enhanced plant drought tolerance [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive studies have showed that plant DNA methylation was predominantly associated with growth and development [30,31], secondary metabolism [32,33] and various stress responses including salt stress [34,35], drought stress [36,37], cold stress [38,39]. Since DNA methylation is involved in regulating a wide range of biological processes, DMT genes have been identi ed and analyzed in several plant species, such as Arabidopsis thaliana [40,41], rice [42,43], maize [44,45], and wheat [46].…”
Section: Introductionmentioning
confidence: 99%